PERBANDINGAN NILAI ECONOMIC VALUE ADDED (EVA) TERHADAP KINERJA KEUANGAN PERUSAHAAN SUB SEKTOR ADVERTISING, PRINTING, DAN MEDIA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Budianto, Shalysa Camila Aini (Jurnal Ilmiah Ekonomi Bisnis, 2023)
The purpose of this study was to determine the comparison of the value of Economic Value Added (EVA) in assessing the financial performance of companies in the Advertising, Printing and Media Sub Sector, namely PT. Graha Layar Prima, Tbk, PT. MD Pictures, Tbk, PT. Jasuindo Tiga Perkasa, Tbk, PT. Tempo Inti Media, Tbk, and PT. Fortune Indonesia, Tbk. The method used is descriptive qualitative analysis, data sources obtained from www.idx.co.id. The technique used is the calculation using Net Operating Profit After Tax (NOPAT), Invested Capital, Weighted Average Cost of Capital (WACC), Capital Charges, and Economic Added Value (EVA). Based on Economic Added Value, PT. Graha Layar Prima, Tbk has the best financial performance because it is able to create value from the cost of capital used. Then followed by PT. Tempo Inti Media, Tbk, PT. Fortune Indonesia, Tbk, PT. MD Pictures, Tbk, and the one with the lowest performance rating is PT. Jasuindo Tiga Perkasa, Tbk.